Source reconstruction without an MRI using optically pumped magnetometer-based magnetoencephalography - Rhodes, Natalie; Rier, Lukas; Boto, Elena; Hill, Ryan M.; Brookes, Matthew J. (Imaging neuroscience (Cambridge, Mass.), 2025)
Source modelling in magnetoencephalography (MEG) infers the spatial origins of electrophysiological signals in the brain. Typically, this requires an anatomical MRI scan of the subject’s head, from which models of the magnetic fields generated by the brain (the forward model) are derived. Wearable MEG—based on optically pumped magnetometers (OPMs)—enables MEG measurement from participants who struggle to cope with conventional scanning environments (e.g., children), enabling study of novel cohorts. However, its value is limited if an MRI scan is still required for source modelling. Here we describe a method of warping template MRIs to 3D structured-light scans of the head, to generate “pseudo-MRIs”. We apply our method to data from 20 participants during a sensory task, measuring induced (beta band) responses and whole-brain functional connectivity. Results show that the group average locations of peak task-induced beta modulation were separated by 2.75 mm, when comparing real- and pseudo-MRI approaches. Group averaged time–frequency spectra were also highly correlated (Pearson correlation 0.99) as were functional connectome matrices (0.87) and global connectivity (0.98). In sum, our results demonstrate that source-localised OPM-MEG data, modelled with and without an individual MRI scan, can be comparable. While individual MRI scans remain the “gold standard” for OPM-MEG modelling, our method will be useful for future studies where MRI data capture is challenging.